How can the Nordic welfare state respond to demographic change? - Jalovaara, Marika; Nisén, Jessica; Lammi-Taskula, Johanna (Edward Elgar Publishing, 2026)
Finland is facing profound demographic changes marked by declining fertility, growing levels of childlessness, and rapid population ageing. This chapter situates these developments in the context of the Nordic welfare model, considering both their social and economic consequences. It examines long-term demographic transitions, differences in fertility by region and educational level, and the role of migration in shaping population change. The authors advocate for a broad, forward-looking policy approach that responds to demographic shifts by investing in human capital and well-being, supporting individuals throughout their life course, and securing the long-term sustainability of society. While strengthening human capital is essential, ensuring social and gender equality is equally crucial to enabling all individuals to reach their full potential in an ageing society. Achieving this will require comprehensive, adaptive, and inclusive policies, complemented by targeted measures, to balance both economic sustainability and social justice and equity in the decades ahead.
Beyond the Nordic Welfare State : Extending Social Investments with Interventions